Exploring age-related differences in the relationship between spatial and temporal contributions to step length asymmetry during split-belt adaptation - Patrick G. Monaghan; William M. Murrah; Kristina A. Neely; Harrison C. Walker; Jaimie A. Roper (Experimental Brain Research, 2024)
Gait adaptability is crucial for meeting environmental demands, and impaired gait adaptation increases fall risk, particularly in older adults. While prior research exists on older adults’ gait adaptation, particularly in perturbation studies, the specific contributions of temporal and spatial adaptation strategies to step length asymmetry (SLA) during split-belt treadmill walking require further examination. This study fills this gap by evaluating how distinct adaptation strategies contribute to SLA in healthy young and older adults. 19 healthy young adults (20.4 ± 1.1 years) and 19 healthy older adults (68.3 ± 8.1 years) walked on a split-belt treadmill requiring their non-dominant leg to move twice as fast as their dominant leg. Repeated measures ANOVA investigated (1) spatial and temporal contributions to SLA, (2) SLA across gait adaptation epochs, and (3) rates of adaptation and deadaptation. Older adults displayed reduced temporal contributions to SLA compared to younger adults (F 1,36 = 6.42, p = .02, ŋ 2 = .15), but no group differences were observed in spatial contributions to SLA (F 1,36 = 3.23, p = .08, ŋ 2 = .082). SLA during adaptation and deadaptation did not differ by age group, nor did the rate of adaptation (F 1,34.7 = 0.594, p = .45) or deadaptation F 1,33.6 = 2.886, p = .09). These findings suggest that while older adults rely less on temporal strategies for gait adaptation, but maintain overall adaptability comparable to younger adults. Findings enhance our understanding of age-related changes in gait adaptation mechanisms and may inform targeted interventions to improve gait adaptability in older populations.